The Poles of Diglossia in Arabic - Janković, Srđan (Prilozi za orijentalnu filologiju, 2017)
The foregoing text deals with the sociocultural identification of what the author terms the poles of diglossia in Arabic (based on the material of language usage in contemporary Egypt). The poles of diglossia are understood to be the H and L varieties established by Ferguson, i. e. two mutually contrasted, structurally highly differentiated idioms, each with strict functional allocations in the speakers' verbal repertoire. Namely, H and L varieties constitute diglossia, but their closes sociolinguistic identification is seen as a prerequisite to a better understanding of the phenomenon of diglossia as such. The H variety is represented by modern literary Arabic. If we want to determine it more closely, we must point out two things: it grew on a foundation of classical Arabic rather than on that of some prestige dialect on the one hand, and its use in the Egyptian sociocultural setting gave rise to variant differences at the standard-language level on the other. It, then, represents a contemporary standard-language realization of literary Arabic, with certain standard variant characteristics in relation to the use of contemporary literary Arabic in other Arab sociocultural settings. In analyzing the L variety in the concrete Egyptian situation, the author has dropped the term “Egyptian colloquial dialect” frequently used in Arabic linguistic studies, because of its diffuseness and the general imprecision in the use of the term “dialect” itself. For, the author claims, such a term could be used for any local dialect or speech on the territory of Egypt and would thus not be an adequate label for the L variety. Using Stewart's sociolinguistic typology of language idioms, the author comes to the conclusion that the L variety is properly represented by the Cairo speech, playing the role of the colloquial semi-standard in all of Egypt. It is hierarchically superposed in respect to all the remaining local types of speech in Egypt, both by the breadth of its usage and by its functional superiority. It is the real representative, within Egypt, of the L variety as the Egyptian vernacular (this term has not yet gained widespread usage in Arabic linguistic studies, especially those practiced in Europe, but has good chances of spreading and replacing the traditional but inadequate term, “the Egyptian colloquial dialect”). The L variety is, thus, vernacularized Cairo speech.